Ageing and longevity genes in cardiovascular diseases. Issue 2 (16th July 2020) - Liberale, Luca; Kraler, Simon; Camici, Giovanni G.; Lüscher, Thomas F.
Abstract: Over the last century, Western societies experienced a demographic shift driven by increased lifespan and decreased fertility, resulting in the subversion of the world's demographic pyramid. In ageing societies, cardiovascular diseases are the major cause of morbidity and mortality, thus representing a major societal and economic burden. Indeed, ageing associates with the deterioration of a genetic network implicated in senescence and longevity, orchestrating deleterious cellular processes that converge in the structural and functional decline of both the myocardium and the vasculature. In this review, we revise a compendium of genes involved in these processes and delineate possible strategies to interfere with them. Dietary interventions (eg intermittent fasting) and sirtuin‐activating compounds are among the most promising interventions shown to promote protective effects on the ageing cardiovascular system. We conclude that ageing and longevity genes modulate cardiovascular function by acting on deleterious downstream processes such as inflammation and oxidative stress, thus representing promising targets for the prevention and treatment of age‐related cardiovascular dysfunction.